A Five Year (2013-2017) Retrospective Study On The Data Of Laboratory Testing For Biocompatibility Of Medical Device Implant Registered With Malaysia Medical Device Authority - Anamalai, Sunthara Murthi (2021)
The study focused on the implantable medical devices which require most number of biocompatibility data. Data collection form reflecting the MeDC@St data entry pages is prepared to manually retrieve the deposited information for registration between July 2013 to December 2017, amounting to 1925 registration with some exceeds 100 pages content per registration.